2003
DOI: 10.1046/j.1471-4159.2003.02028.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate formation in the spinal cord of mutant SOD1 transgenic mice is reversible and mediated by proteasomes

Abstract: Cu,Zn superoxide dismutase (SOD1) mutations cause one form of familial amyotrophic lateral sclerosis by a toxic gain of function that may be related to abnormal protein folding and aggregate formation. However, the processing pathways involved in SOD1 aggregate generation within spinal cord remain unclear. We have now developed an experimental system for studying SOD1 aggregate formation and clearance in intact spinal cord tissue. Here we demonstrate that the formation of SOD1-positive aggregates in G93A SOD1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 31 publications
2
42
0
1
Order By: Relevance
“…That these aggregates are central to the pathogenesis of disease forms the basis for the aggregation or protein mishandling model of ALS (Kabashi and Durham, 2006). Much experimental evidence has found that mutant SOD1 and its aggregates are cleared by proteasome mediated degradation pathways raising the possibility that alterations in proteasome function in vivo might influence the rate of aggregate accumulation and change disease course (Johnston et al, 2000;Puttaparthi et al, 2003;Di Noto et al, 2005). Several groups have found that there is induction of immuno-proteasomes in the spinal cords of mutant SOD1 transgenic mice as they develop neurological dysfunction suggesting a potential compensatory role for immuno-proteasomes as a response to the increasing accumulation of SOD1 aggregates (Cheroni et al, 2005;Puttaparthi and Elliott, 2005;Ahtoniemi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That these aggregates are central to the pathogenesis of disease forms the basis for the aggregation or protein mishandling model of ALS (Kabashi and Durham, 2006). Much experimental evidence has found that mutant SOD1 and its aggregates are cleared by proteasome mediated degradation pathways raising the possibility that alterations in proteasome function in vivo might influence the rate of aggregate accumulation and change disease course (Johnston et al, 2000;Puttaparthi et al, 2003;Di Noto et al, 2005). Several groups have found that there is induction of immuno-proteasomes in the spinal cords of mutant SOD1 transgenic mice as they develop neurological dysfunction suggesting a potential compensatory role for immuno-proteasomes as a response to the increasing accumulation of SOD1 aggregates (Cheroni et al, 2005;Puttaparthi and Elliott, 2005;Ahtoniemi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Puttaparthi et al, 2003;Di Noto et al, 2005). Early in vitro work with protein aggregates had predicted that proteasome function might be inhibited in neurodegenerative diseases, but studies using transgenic rodent models of Huntington's disease and ALS found that instead there appeared to be induction of proteasome activity within the CNS as the animals developed neurological disease (Bence et al, 2001;Diaz-Hernandez et al, 2003;Kabashi et al, 2004;Cheroni et al, 2005;Puttaparthi and Elliott, 2005;Ahtoniemi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Mutant SOD1 may cause excitotoxicity in motor neurons by inducing mitochondrial dysfunction and impairing glial glutamate transporter function (45,46). Additionally, mutant SOD1 causes disorganization of the cytoskeleton and disrupts axonal transport (47,48), compromises proteasome activity (37,49), (which in turn causes accumulation and aggregation of mutant SOD1 (35,50)), and induces inflammation (51-54) (which may accelerate the disease progression (55)(56)(57)). These downstream effects of mutant SOD1 presumably trigger the final programmed cell death in motor neurons (58).…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…Ten percent of ALS cases are familial (fALS), with 20% of fALS being linked to mutations in the homodimeric protein Cu/Zn superoxide dismutase 1 (SOD1) (6-8). In animal models and in humans carrying SOD1 mutations, mutant SOD1 is "toxic" only to motor neurons, and only after it has been present for an extended period (aging), leading to the important questions of how mutant SOD1 exerts its toxicity and why motor neurons are particularly sensitive to the pathogenic process.Mutant SOD1 has a high propensity to undergo conformational changes and aggregation when stressed in vitro, and SOD1 aggregates and misfolded aggregate precursors have been localized specifically to pathologically affected tissues in animal models of disease, suggesting that SOD1 conformational changes may contribute to the toxicity of the mutant protein (9)(10)(11)(12)(13)(14). It has been further demonstrated that conformational changes in wildtype SOD1 can be induced through oxidation and/or metal depletion and that these conformers of the wild-type protein are also toxic in cellular models (15-18).…”
mentioning
confidence: 99%